PEMANFAATAN POTENSI LOKAL WORTEL DALAM PEMBUATAN BOLU SEBAGAI UPAYA PEMBERDAYAAN UMKM DESA GONGSOL - Aulia, Muhammad Fitra; Fy, Muhammad Fathir; Natasyah, Natasyah; Sungkar, Audira Luthfia; Kamalia, Lailatun Nur (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2025)
The Community Service Program (KKN) of the State Islamic University of North Sumatra, which was carried out in Gongsol Village, Karo Regency, is one of the efforts to optimize local potential based on agricultural products. Gongsol Village is known as a center for carrot production, but its utilization has so far been limited to fresh sales with relatively low economic value. Through this KKN activity, students provided assistance and training to the community in processing carrots into value-added products in the form of carrot cake. The research used a qualitative approach with a case study method, where data was obtained through participatory observation, in-depth interviews, documentation, and literature studies. The stages of the activity included identifying potential, testing the production of carrot cake with the involvement of culinary experts, analyzing economic feasibility, and developing a digital-based marketing strategy and collaboration with souvenir shops. The results of the study show that carrots have high nutritional content, especially beta-carotene, which is beneficial for health and makes them a potential raw material for functional food products. Through the innovation of carrot cake, the community not only gets an alternative healthy processed product, but also gains new business opportunities that can increase income and strengthen village MSMEs. Through collaboration between students, the village government, and the local community, this program is expected to create business sustainability through training and periodic evaluations, enabling Gongsol Village to independently manage its agricultural potential.